L'Italia alla fine del Medioevo II I caratteri originali nel quadro europeo II - Cengarle, Federica (Centro di Studi sulla Civiltà del Tardo Medioevo San Miniato, 2006)
This is the second of two volumes examining some "original features" of late medieval Italy compared to the european reality of the time (the first volume of this collection was edited by Francesco Salvestrini). On this subject, two conferences have been held, whose proceedings have been published. The first conference, held in October 2000, tried to offer an account, in an introductory section, of the long-term environmental frameworks within which the path of Italian society is inscribed: the rural landscape and the framework of urban settlements, without forgetting, in one and in the another case, the legacy of the Roman world. The second conference, on the other hand - held in the autumn of 2002 - aimed to consider aspects of the history of culture and political ideologies, mentality, religious life, but also the history of techniques.